1992
DOI: 10.1103/physrevlett.69.2276
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy of aBi2Sr2et al.

Abstract: New magnetic torque measurements on a high-quality Bi2Sr2CaCu20a; single crystal show that only a lower bound for the anisotropy parameter 7 > 150 can be given. For misorientations of the field H from the (a, b) plane larger than 0.5°, the results can be rescaled to magnetization M vs H. The behavior of M can be consistently described by a recent theory of Bulaevskii, Ledvij, and Kogan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
54
0
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(60 citation statements)
references
References 15 publications
5
54
0
1
Order By: Relevance
“…Torque magnetometry has already proven itself to be a powerful tool for measuring the equilibrium properties and for studying the dimensionality of the vortex system. 9 By comparing our results with superconducting quantum interference device ͑SQUID͒ measurements, it is shown that the occupation of columnar tracks by pancake vortices only depends on the field component parallel to the sample c axis, i.e., the distribution of pancakes depends only on the pancake density and not on the field direction. It means that the total pinning energy increases, and hence, that free pancakes are removed, not created, as the field is tilted away from the irradiation direction.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Torque magnetometry has already proven itself to be a powerful tool for measuring the equilibrium properties and for studying the dimensionality of the vortex system. 9 By comparing our results with superconducting quantum interference device ͑SQUID͒ measurements, it is shown that the occupation of columnar tracks by pancake vortices only depends on the field component parallel to the sample c axis, i.e., the distribution of pancakes depends only on the pancake density and not on the field direction. It means that the total pinning energy increases, and hence, that free pancakes are removed, not created, as the field is tilted away from the irradiation direction.…”
mentioning
confidence: 92%
“…The contribution ϪM x H z can therefore be neglected; the z component of the magnetic moment can be obtained by simply dividing the torque by the field component parallel to the sample, H x ϭH a cos ⌰, where ⌰ is the angle between the field and the ab plane. 9 Figure 1 shows the raw data of a torque experiment at 76 K ͑applied fields are indicated͒. No irreversibility is observed except for very small angles where the field orientation approaches the ab plane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Second, the linear geometry of the ion tracks results in the effective alignment of the pancake vortices along the tracks, and the re-establishment of interlayer superconducting phase coherence at temperatures and fields where the unirradiated material behaves as a stack of nearly decoupled superconducting layers. 4,7,[22][23][24][25] The pancake vortex alignment is manifest in the angular dependence of the transport properties of the irradiated superconductor, 4,6 as well as in measurements of the c-axis conductivity (perpendicular to the superconducting layers) 9,10,26,27 and of the field at which the Josephson plasma resonance occurs in the range 24 -45 GHz. 11,12,28,29 Measurements of the Josephson plasma resonance and of the c-axis conductivity, 26,27 which have the advantage of directly probing the Josephson critical current and the cosine of the average phase difference between layers, show the existence, in the heavy-ion irradiated layered superconductor Bi 2 Sr 2 CaCu 2 O 8+δ , of a regime B l (T ) < B < B h (T ) in the vortex liquid state in which interlayer superconducting phase coherence increases as the magnetic field is increased (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…No hysteresis was found within our experiments accuracy in magnetic field above 0.5 Τ and Τ > 75.5 Κ. However the shape of peak and its position was found to be a slight function of temperature and magnetic field similarly to the results of paper [9]. Interpretation of the torque data within Kogan's formula [2] is open to discussion.…”
Section: Introductionmentioning
confidence: 53%